Finding the Role of Elevated Antinuclear Antibodies (ANA) in Diagnosis and Treatment of Medically Critically Ill Patients - Tayyaba Nazir, Iqra Shahnwaz, Ammara Zafar, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Antinuclear antibody (ANA) testing is an important screening tool for autoimmune conditions, such as systemic lupus erythematosus (SLE) and scleroderma. Objectives: Finding the role of elevated antinuclear antibodies (ANA) in diagnosis and treatment of medically critically ill patients. Material and methods: This cross sectional study was conducted THQ Hospital, Muree during July 2021 to November 2021. The data was collected from 600 patients of different diseases. In patient with multiple hospitalizations, the most recent one was considered for the study. Results: The data was collected from 600 patients had their ANA levels drawn, out of which 78 were positive and 522 were negative. Out of the ANA positive patients, 14 (17 percent) had the values to 1:40, 29 (35 percent) had values to 1:80, 14 (17 percent) had values to 1:160, 8 (9.7 percent) had values to 1: 320, 11 (13.2 percent) had values to 1:640, 4 (4.8 percent) had values to 1:1280, 2 (2.4 percent) had values greater than >1:1280. Conclusion: It is concluded that in patients with RA, important differences exist between those who are ANA‐positive and ANA‐negative in terms of time to fulfillment of RA criteria and time to DMARD initiation as well as choice of initial pharmacotherapy.